Finite-Element Analysis on the Tensile Membrane Effect in Geogrid Reinforced Piled Embankment under Dynamic Loading - Yan Zhuang; Kangyu Wang; Shunlei Hu; Xidong Zhang; Xiaoyan Cui (Geofluids)
This study presented a numerical investigation of the tensile membrane effect in the geogrid reinforced piled embankment under dynamic loading. It has been found that the maximum sag of the geogrid was attained at the center of two adjacent piles, while localization of tensile force was observed at the corners of the pile caps. Under the dynamic loading, the sag and the strain of the geogrid increased when compared with the static loading, an increase of around 45.9% and 24% was, respectively, yielded for the sag and the strain of the geogrid. This increase of tension in the geogrid may mainly result from the degradation of the soil arching effect under dynamic loading. A parameter study was performed, and it showed that the tensile force in the geogrid increases with the rise of the embankment height, the clear pile spacing, and the tensile stiffness of the geogrid. However, the increase of the friction angle of the embankment fill led to a decrease in the tension in the geogrid, which may benefit from the improvement of the soil arching developed in the embankment fill. It was found that the tensile behavior of the geogrid was the most sensitive to the pile spacing. When pile spacing increased from 2.0 m to 3.0 m, the tensile force in the geogrid increased by about 248%.